La Unión Monzogranite: geochronology and significance of the Jurassic arc in the Sula Terrane, Guatemala - Francis Emanuel Salguero-Díaz; Luigi A. Solari; Osmín J. Vásquez; Ricardo Enrique Milián de la Cruz; Carlos Ortega-Obregón (Revista Mexicana de Ciencias Geológicas)
La Unión pluton (LUP) belongs to the metamorphic and igneous Sula Terrane (ST) of Central Guatemala, limited to the north by the Motagua fault (MF) and to the south by the Jocotán-Chamelecón fault system (J-CH-FS). The basement of the ST is characterized by the high-grade metamorphic rocks belonging to the Las Ovejas Complex and the extensive low-grade San Diego phyllite, the latter in tectonic contact with LUP. A combination of field data, petrographic and geochemical analyses as well as geochronologic dating by U-Pb method, allow to classify LUP as a monzogranite with an age of 170 Ma (average of two dated samples), characterized by high-K calcalkaline and peraluminous affinity and with a REE pattern typical of a continental magmatic arc. Some trace-elements behavior and a comparison of similar-age units found elsewhere in eastern, central and southern Mexico, allow to associate its formation to the lithospheric thinning and extension that occurred during the breakup of Pangea and the opening of the Gulf of Mexico.